Nd:YAG Laser Hialoidotomi sebagai Tatalaksana Perdarahan Premakular Subhialoid pada Pasien Leukemia Anak: Laporan Kasus - Ade J. Nursalim; Vera Sumual; Andrew Citra; Elbetty Simanjuntak; Christian Komaling; Stevanus Loho (Universitas Sam Ratulangi, 2023)
Abstract: Premacular subhyaloid is a condition that results in a severe decrease in visual acuity, especially if it occurs in the area around the macula. This subhyaloid premacular hemorrages often occurs in acute lymphoblastic leukemia. Nd:YAG laser hyaloidotomy is a non-invasive therapy option to treat this condition. We reported a case of a 15-year-old boy who came with a complaint of blurred right eye. The patient had a history of acute lymphoblastic leukemia. Visual acuity was 1/60 in the right eye and 6/9 in the left eye. A dome-shaped subhyaloid hemorrhage was found in the right eye and then was treated with Nd:YAG laser hyaloidotomy. The results of therapy were seen in improvement of vision after one week of therapy. In conclusion, Nd:YAG laser hyaloidotomy is a non-invasive procedure that is relatively safe, and improvement of vision can be observed in a short time, in this case, within one week. Keywords: Nd:YAG laser; hyaloidotomy; subhyaloid premacular hemorrages; acute lymphoblastic leukemia Abstrak: Perdarahan premakular subhialoid merupakan kondisi yang mengakibatkan turunnya tajam penglihatan yang hebat terutama jika terjadi di daerah sekitar makula. Perdarahan premakular subhialoid ini sering terjadi pada leukemia limfoblastik akut. Nd:YAG laser hialoidotomi merupakan salah satu terapi non invasif untuk mengatasi keadaan perdarahan ini. Kami melaporkan kasus seorang anak laki-laki berusia 15 tahun dengan keluhan mata kanan kabur mendadak. Pasien dengan riwayat leukemia limfoblastik akut. Tajam penglihatan 1/60 pada mata kanan dan 6/9 pada mata kiri. Ditemukan perdarahan subhialoid berbentuk kubah pada mata kanan dan dilakukan terapi Nd:YAG laser hialoidotomi. Hasil terapi memperlihatkan perbaikan tajam penglihatan setelah satu minggu terapi. Simpulan kasus ini ialah terapi Nd:YAG laser hialoidotomi merupakan prosedur non- invasif yang relatif aman dan perbaikan tajam penglihatan dapat terlihat dalam waktu singkat yaitu dalam kurun waktu satu minggu Kata kunci: Nd:YAG laser hialoidotomi; perdarahan premakular subhialoid; leukemia limfoblastik akut